Soil physics properties and their relation to different levels of forage suply on a natural pastures - Bertol, Ildegardis; Ellera Gomes, Klecius; Berenice Nicoloso Denardin, Rosiane; Armando Zago Machado, Luis; Ernesto Maraschin, Gerzy (Pesquisa Agropecuaria Brasileira, 1998)
Animal management with different allotment can affect some important soil physical properties on natural pastures, increasing soil susceptibility to water erosion and decreasing its productive capacity. Therefore, more information about the relationships among soil, plant and animal are necessary to improve to sustainability in the use of natural pastures. The experiment was conducted in 1993, with the objetive of evaluating soil aparent density, total porosity, pore diameter distribution, weighed average diameter of aggregates, water infiltration rate on natural pasture submitted to different animal allotments. Four levels of forage supply were studed: 4, 8, 12 and 16%, on soil sandy loam red-yellow podzolic (Paleudult). The results showed a significant decrease on soil water infiltration rate in the lower levels of forage supply (4 and 8%). There was also a trend of decreasing total porosity and weighed average diameter of aggregates and of increasing soil aparent density in treatments with higher grazing pressure and lower forage availability. Calcium and magnesium contents were lower at the first 3 cm of the soil under 4% of forage supply than in the other treatments.